The Society 5.0 Concept: A Framework for Societal Evolution - Nepal, Ananda; Prajapati, Mamata (International Research Journal of MMC, 2025)
The study focuses on the idea of Society 5.0 as a comprehensive framework for understanding the development of human societies through various technological and socio-economic shifts. It traces Nepal's historical journey from early hunter-gatherer societies (Society 1.0) to the upcoming data-driven and AI-enhanced future (Society 5.0). The article describes key historical changes, such as the use of metal, the introduction of farming machines, the rise of factories, and advances in digital technology. It discusses the specific challenges and opportunities in Nepal and explains how technologies like Artificial Intelligence, automated systems, and smart infrastructure can help build a better society by prioritizing people's well-being and sustainable progress. This study is based on a general review used a narrative approach to analyze sources on Society 5.0 from 2018–2024, focusing on technology, social change, and policy in infrastructure, education, governance, and socio-economic development. The study emphasizes the need for strategic policymaking, infrastructure development, and inclusive technology adoption to fully harness the potential of Society 5.0, providing valuable insights for policymakers, researchers, and practitioners working to guide societies toward smarter and more resilient futures.